Comparison of different anticoagulation methods in continuous renal replacement therapy for pediatric acute liver failure patients: a retrospective observational study - He, Jie; Zhang, Xinping (Frontiers in Pediatrics, 2025)
ObjectiveOptimal anticoagulation for pediatric acute liver failure (ALF) patients requiring continuous renal replacement therapy (CRRT) remains challenging due to concurrent bleeding risk and hypercoagulability. This study aimed to evaluate the efficacy and safety of various anticoagulation strategies in pediatric ALF.MethodsWe retrospectively analyzed 51 children with ALF from January 2017 to December 2023. Patients were grouped based on anticoagulant: systemic heparin anticoagulation group (SHA group, n = 19), regional citrate anticoagulation group (RCA group, n = 15), and nafamostat mesylate group (NM group, n = 17). Primary outcomes were filter lifespan and the incidence of new clinical bleeding episodes.ResultsFilter lifespan was shortest in the SHA group but similar between the RCA and NM groups [SHA: 37.0 [34.0, 42.0] h; RCA: 43.0 [39.0, 49.0] h; NM: 43.0 [40.5, 48.0] h; P = 0.003]. The SHA group experienced a significantly higher rate of new bleeding episodes (36.8%) compared with the RCA (6.7%) and NM (5.9%) groups (P = 0.036). Metabolic alkalosis and hypocalcemia were more frequent in the RCA group (46.7% vs. 10.5% vs. 11.8%; P < 0.001). Multivariate Cox regression showed that, relative to SHA, both RCA and NM significantly reduced filter clotting risk (HR = 0.108, 95% CI 0.047–0.248, P < 0.001). Additionally, higher pre-CRRT platelet count (HR = 1.014, 95% CI 1.007–1.021, P < 0.001), and higher initial transmembrane pressure (HR = 1.168, 95% CI 1.104 −1.236, P < 0.001) were associated with increased clotting risk.ConclusionIn ALF children undergoing CRRT, both RCA and NM demonstrate superior filter longevity and bleeding safety compared to heparin. NM may be preferred due to fewer metabolic disturbances than RCA.